Tekhnologiya uskorennogo obucheniya plavaniyu - Bykov, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
Pedagogical technology of quickened instructing in sports swimming was elaborated by the author for the students of physical culture institutes and academies. Methodical scheme of the technology includes five stages. Methods and means of instructing are used in dependence of specific technical purposes wishful for each stage. Technical instructing in all kinds of sports swimming (crawl, dolphin, breast-stroke) was performed simultaneously, but by separate elements. Advantages of complex instruction in sports swimming were experimentally approved. Given technology makes favorable conditions for quickened instructing in sports swimming and provides effective technical skills acquirement for the considerably short time.